2022
DOI: 10.21603/2308-4057-2022-1-127-136
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme complexes for activating yeast generation and ethanol fermentation

Abstract: Introduction. Recent studies have shown the benefits of phytolytic enzymes to prepare grain wort in ethanol production. However, there is a lack of data on the effect of phytases and their amount on the conversion of grain polymers, the ionic composition of wort and mash, and the efficiency of yeast generation and ethanol fermentation. Study objects and methods. Wheat and corn wort samples were treated with a complex of hydrolases, including phytases. Capillary electrophoresis determined the ionic compos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…The analysis and quantification of the ionic composition by CE coupled to a conductometric detector during the optimization of the fermentation process allowed defining the behavior of the yeast activity and metabolism accordingly to the addition of different enzyme complexes to select the optimal enzyme mixture that maximized the ethanol production and minimized the formation of fermentation by‐products. In that way, it was observed that the phytase and protease enzymes promote the accumulation of phosphates and minerals available for yeast metabolism, giving rise to an increase in the ethanol synthesis yield [115]. Another relevant role of CE during the food processing was described by Marcondes et al.…”
Section: Food Processing and Storagementioning
confidence: 99%
“…The analysis and quantification of the ionic composition by CE coupled to a conductometric detector during the optimization of the fermentation process allowed defining the behavior of the yeast activity and metabolism accordingly to the addition of different enzyme complexes to select the optimal enzyme mixture that maximized the ethanol production and minimized the formation of fermentation by‐products. In that way, it was observed that the phytase and protease enzymes promote the accumulation of phosphates and minerals available for yeast metabolism, giving rise to an increase in the ethanol synthesis yield [115]. Another relevant role of CE during the food processing was described by Marcondes et al.…”
Section: Food Processing and Storagementioning
confidence: 99%